Public Health - Social and Behavioral Health 2012
DOI: 10.5772/37369
|View full text |Cite
|
Sign up to set email alerts
|

Economic Stressors and Childhood Obesity: Differences by Child Age and Gender

Abstract: Hard cover, 570 pagesPublisher InTech

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…McKenzie (2012), in her study of working-class life on a Nottingham council estate, found that “women’s lives were full of risk management” in the everyday, and that they included stigmatisation (2012, p. 131). As with Garasky et al’s (2012) research in the United States, the “everyday” in this data, included financial and environmental stresses that they found associated with obesity in children. These authors suggest that there is less control over food choices in such scenarios of poverty (2012, p. 127).…”
Section: Discussionmentioning
confidence: 99%
“…McKenzie (2012), in her study of working-class life on a Nottingham council estate, found that “women’s lives were full of risk management” in the everyday, and that they included stigmatisation (2012, p. 131). As with Garasky et al’s (2012) research in the United States, the “everyday” in this data, included financial and environmental stresses that they found associated with obesity in children. These authors suggest that there is less control over food choices in such scenarios of poverty (2012, p. 127).…”
Section: Discussionmentioning
confidence: 99%